STIGMA KELUARGA TERHADAP ANGGOTA KELUARGA YANG MENDERITA SKIZOFRENIA DI UNIT RAWAT JALAN RUMAH SAKIT JIWA GRHASIA DAERAH ISTIMEWA YOGYAKARTA - Zalita Putriana; Dewi Retno Pamungkas; Puji Sutarjo (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background:Stigma is a wrong belief, which is more likely based on emotional reaction to isolate and punish individual who actually need help. Stigma of a family toward their family members will impact on the recovery of patient with schizophrenia. Objective:To explore the family stigma toward family members with schizophrenia in out patient unit of Grhasia Psychiatric Hospital in Yogyakarta Special Region. Method:This research was descriptive with the use of a questionnaire. The data collecting technique was purposive sampling with the number of samples of 98 respondents. Result:Family stigma toward family members withs chizophrenia was viewed from several faktors, they were education, gender, age, andtribe. Stigma was measured into three categories: namely low, medium, and high. Conclusion:Stigma was measured into three categories; there were 4 respondents (4,1%) with low stigma, 79 respondents (80,6%) with medium stigma, and 15 respondents (15,3%) with high stigma. Most of the family have medium stigma toward family members with schizophrenia. Keyw ords: Stigma, schizophrenia, family.